A MEKANISME PENGGUNAAN MEMBER CARD ALFAGIFT DALAM JUAL BELI PERSPEKTIF HUKUM ISLAM (Studi Kasus di Alfamart Ponorogo) - Muhammad Nur Fadli; Ahmad Syafi'i SJ; Nafiah Nafiah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
In this digital era, with the frequent advancement of technology and information, people tend to be more interested in everything that is practical, effective and efficient in every activity they carry out. The same applies to buying and selling transactions in the community economy, where the majority of people choose the easy and hassle-free option in order to increase their purchasing power. Therefore, many shops or shopping malls offer membership cards or Member Cards which are referred to in Arabic as Bithaqatuat Takhfidh. With the formulation of the problem: (1) What is the mechanism for using the Alfagift Member Card in buying and selling at Alfamart Ponorogo. (2) What is the view of Islamic law regarding the use of the Alfagift Member Card in buying and selling at Alfamart Ponorogo. This research is a qualitative type of research that is descriptive in nature. The sources of information for this research are Alfamart and Alfamart consumers. Data collection techniques carried out by this researcher included observation, interviews, and documentation. Analysis techniques use data collection, data reduction, data presentation, drawing conclusions and verification. The results of this study are the use of the Alfagift Member Card at Alfamart Ponorogo. Based on the results of interviews with Alfamart consumers, it was found that the presence of Alfagift member cards made it easy for their owners. Alfagift card member users will get various benefits, such as discounts, collection of points, shopping vouchers, gifts, and others. Alfagift member card users will also collect points that can be exchanged for various offers provided by the company. So that the existing data states that the essence of buying and selling transactions using the Alfagift member card has fulfilled the trading requirements and does not contain elements of gharar (uncertainty), speculation and fraud. There is no element of coercion between buyers and sellers, and the goods sold are clear and provide benefits to consumers.